Pemeriksaan Tes Cepat Molekuler pada Pasien Suspek TB Paru di Puskesmas Ngadirejo, Temanggung - Azam Mustajab, Abdullah; Husni Kuswanto, Cuk; Paramastui Azuma, Anindita; Indriani, Farihah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Tuberculosis became a deadly infectious disease in the world. The disease is mostly contributed by adults, with the remainder donated by children. As another problem arises, people are resistant to anti-tuberculous drugs. These conditions require steps in accurate diagnosis so that proper treatment can be given and no fatal problems occur later. One way of diagnosing tuberculosis is by examining Molecular Quick Tests because of its high sensitivity and specificity and its results can be known faster. The purpose of this study illustrates the results of TCM examination on pulmonary TB suspect patients at the Public Health Center Ngadirejo, Temanggung. The research method is a descriptive quantitative with cross sectional approach to observing secondary data from TCM examinations on suspected pulmonary TB patients examined in January–November 2022. The results of the study showed that of 463 patients with suspected pulmonary TB who underwent TCM examination, 455 (98,27%) had negative MTB patients, 7 (1,51%) sensitive rifampicn MTB patients, and there was 1 (0,22%) patient who was detected to be rifampicin resistant. The conclusion of TB disease is still a serious problem, in addition to active TB problems, latent TB problems, MDR-TB and XDR-TB problems. Research findings suggest sensitive pulmonary rifamycin, pediatric pulmonary TB and rifampycin-resistant pulmonary TB.